Implementation of Laws Number 8 of 2016 Concerning Disabilities Persons in Bandar Lampung City in 2022 - Maya Zulvi Astarida; Zainudin Hasan (Activa Yuris: Jurnal Hukum, 2021)
Philosophical and constitutional based on Pancasila and UUD 1945, each citizen had equal work opportunities, access public facilities, acquire a decent life, including those with disabilities. Law number 8 year 2016 on disabilities person emphasizes that "disability is part of the Indonesian people of equal position, right, obligation and role." The writing use a normative-qualitative juridical approach study method and a qualitative descriptive study method. The reality of fulfilling disability rights remains very limited. People with disability do not have a good level of education and often get a bad stigma from people in general. The implementation of policy has several adverse factors: implementation of policy failed because of the undisclosed nature of policy, the implementation of public policy is very difficult, for example because of communications disruption, the implementation of public policy will be difficult if not enough support, the sharing of potential among the perpetrators involved in implementation